Scrub Typhus Meningoencephalitis: An Uncommon Cause of Acute Febrile Encephalopathy in the Elderly - Lekshmi V Kesavan Nair; Rajani K Timmalsugur; Vishal Mangal (Journal of Marine Medical Society, 2022)
Central nervous system infections are an uncommon cause of acute febrile encephalopathy (AFE) in the elderly. Scrub typhus meningoencephalitis is uncommon and often missed in the elderly. A 70-year-old male presented with complaints of intermittent fever, maculopapular rash, and altered sensorium. Physical examination revealed fever, tachycardia, tachypnea, maculopapular rash on the trunk, and all four limbs, and an eschar on the right thigh. Initial laboratory evaluation revealed anemia, thrombocytopenia, and azotemia. The cerebrospinal fluid revealed lymphocytic pleocytosis, elevated proteins with normal glucose, and adenosine deaminase. Weil–Felix test was positive. The diagnosis of scrub typhus meningoencephalitis with acute kidney injury and atypical pneumonia was established. A prompt treatment with injection doxycycline and tablet rifampicin led to an uneventful recovery. We report the first case of scrub typhus meningoencephalitis as the cause of AFE in the elderly. This case highlights the importance of clinical examination in any febrile encephalopathy presenting in endemic areas or travelers returning from such places.